Stress and Medication Adherence in Elderly People with Hypertension in the Public Health Center of Kassi-Kassi, Makassar - Saputri, Shelvina Adella; Malasari, Silvia; Rahman, Framita (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2024)
Background: Stress that occurs in elderly people with hypertension will result in an increase in blood pressure, which will trigger hypertension. If stress is not treated immediately, it will trigger complications. The impact of stress on the elderly with hypertension greatly affects the quality of life, well-being, and self-care regarding medication compliance. Optimal treatment compliance is a contributing factor in controlling blood pressure in hypertension. Without medication compliance, taking anti-hypertension medication alone will not provide sufficient results in managing and controlling blood pressure. Aim: This study aims to determine the relationship between stress levels and compliance with taking anti-hypertension medication in elderly people in the Kassi Kassi Public Health Center, in Makassar Method: This is a quantitative study with a cross-sectional approach, the PSS-10 (Perceived Stress Scale), and MMAS-8 (Morisky Medication Adherence Scale) as questionnaire instruments, with a purposive sampling technique. The respondents in this study were 126 elderly people Results: Based on the results of statistical tests using the Spearman rank test and a significance level of α = 0.05, the p-value = 0.00 is smaller than α or 0.00 < 0.05, which means there is a relationship between stress levels and compliance with taking antihypertensive medication in elderly people in the Kassi Kassi Public Health Center, Makassar. Conclusion: It is concluded that there is a relationship between stress levels and compliance with taking antihypertensive medication in elderly people in the Kassi Kassi Public Health Center, Makassar.